Search for environmental effects on the KLL Auger spectrum of rubidium generated in radioactive decay. (9th January 2015) - Inoyatov, А Kh; Perevoshchikov, L L; Kovalík, A; Filosofov, D V; Yushkevich, Y V; Ryšavý, M; Lee, B Q; Kibédi, T; Stuchbery, A E; Zhdanov, V S
Abstract: The KLL Auger spectrum of rubidium following the electron capture (EC) decay of 83 Sr and 85 Sr isotopes was experimentally studied in detail for the first time using one 83 Sr source and three 85 Sr sources in different host matrices. Energies, relative intensities, and natural widths of all the nine well-resolved basic spectrum components were determined and compared with both predictions and experimental data for krypton. The results of our multiconfiguration Dirac–Fock calculations demonstrated an influence of the 'atomic structure effect' on absolute energies of the KLL transitions following the creation of initial vacancies by the EC decay. Environmental effects on the KLL Auger spectrum were distinctly observed only for the absolute transition energies.